2013
DOI: 10.2298/sarh1312794a
|View full text |Cite
|
Sign up to set email alerts
|

Family planning among women in urban and rural areas in Serbia

Abstract: Our study showed that there were differences in terms of family planning between the women of urban and rural areas, however, these differences could be explained by differences in age and education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 16 publications
0
5
0
3
Order By: Relevance
“…Of all contraception methods representing the risk factors of the cervical carcinoma, usage of oral contraceptives was most frequently analysed and as a protection factor, persistent usage of condoms. This study confirmed that persistent usage of condoms is not the risk factor and in Serbia a small number of women use pills so that their effect was not analysed (National Health Survey for the population of Republic of Serbia 2006; Antic et al, 2013). Risk of the cervix uteri carcinoma is in positive correlation with the time period of oral contraceptives (OC) usage (Castellsague and Munoz, 2000;Smith et al, 2003;Kjellberg et al, 2008).…”
Section: Discussionmentioning
confidence: 52%
“…Of all contraception methods representing the risk factors of the cervical carcinoma, usage of oral contraceptives was most frequently analysed and as a protection factor, persistent usage of condoms. This study confirmed that persistent usage of condoms is not the risk factor and in Serbia a small number of women use pills so that their effect was not analysed (National Health Survey for the population of Republic of Serbia 2006; Antic et al, 2013). Risk of the cervix uteri carcinoma is in positive correlation with the time period of oral contraceptives (OC) usage (Castellsague and Munoz, 2000;Smith et al, 2003;Kjellberg et al, 2008).…”
Section: Discussionmentioning
confidence: 52%
“…Sırbistan'daki çalışmada kentsel ve kırsal alanda yaşayanların aile planlaması yöntem tercihleri de incelenmiş ve kırsal bölgede kondom tercihinin kentsel bölgeye oranla daha az olduğu saptanmıştır. [10] Yunanistan'da yapılan bir çalışmada da, şehirde yaşayan kadınların aile planlaması yöntemlerini oldukça düşük düzeyde kullanmakta oldukları bulunmuştur. [13] Özel sektörün desteklemesine rağmen 1980'li yıllarda üreme çağındaki kadınların sadece %2'sinin aile planlaması için ilgili merkezlere başvurduğu ve 2001 yılından sonra oranlar olumlu yönde değişse bile, halen küretajın aile planlaması yöntemi gibi kullanıldığı belirtilmektedir.…”
Section: Yöntem Tercihleriunclassified
“…[14] Sırbistan'daki çalışmada da tüm yaş gruplarındaki kadınların en sık geleneksel yöntemleri tercih ettikleri, 20-29 yaş grubunun kondom ve geri çekme yöntemi tercihlerinin daha yüksek olduğu saptanmıştır. [10]…”
Section: Yaşın Etkisiunclassified
See 1 more Smart Citation
“…Dynamics in family members and role vary from country to country depending on a number of internal and external factors, such as legislation, religion, culture, traditions, society, etc. (1)(2). Reproductive health and intentions are important elements of the overall health concept.…”
Section: Introductionmentioning
confidence: 99%